Effects of excavation unloading on the energy-release patterns and stability of underground water-sealed oil storage caverns. (January 2017) - Zhuang, D.Y.; Tang, C.A.; Liang, Z.Z.; Ma, K.; Wang, S.Y.; Liang, J.Z.
Abstract: Large-scale underground water-sealed oil storage caverns have become an important method for storing strategic crude oil reserves worldwide. Previous studies have focused on the stability of the surrounding rock masses during excavation processes. In this study, a microseismic monitoring system was installed in the 1N and 1S Oil Storage Grottos (OSGs) of the Jinzhou underground water-sealed oil storage caverns. The major goals of this study were to investigate the temporal-spatial evolution of the micro-cracks and energy-release patterns induced by excavation unloading in surrounding rock masses. The measured waveforms were interpreted via the time-frequency combined analysis method. The results show that the excavation blasting damage range in the Jinzhou underground storage caverns was about 120 m. The local instability phenomena (e.g., "cavity collapses") occurred in the vicinity of a mileage location of 2 + 45–2 + 55 m in the southern sidewall of the middle layer of the 1N OSG due to the energy-release in the surrounding rock masses resulting from excavation unloading. Excavation unloading induced the formation and localization of micro-cracks, which eventually produced local rock failure. Also, the energy-release patterns in the surrounding rock masses and the relationship between stability and those are revealed, providing a reference for identifying, delineating and predicting potential danger areas in the surrounding rock masses for underground water-sealed oil storage caverns.